2009
DOI: 10.1016/j.ygcen.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of prolactin in avian molt: The effects of gender and breeding success on the timing of molt in Mute swans (Cygnus olor)

Abstract: The aim of the study was to test the hypothesis that decreasing plasma prolactin stimulates or permits the initiation of avian molt. Changes in the concentration of plasma prolactin in Mute swans (Cygnus olor) were compared in non-breeding singletons and breeding pairs. In breeding swans, the onset of molt is delayed compared to non-breeders, and is delayed further in breeding males compared to their female partners. The seasonal decrease in prolactin in non-breeding birds of both sexes started at the end of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…One possibility is that brighter white females obtain nest sites located closer to prime foraging areas and are in better condition and able to mount a stronger immune response as a result. At a proximate level, it is possible that sex differences in the timing of molt (Hemborg, 1999;Dawson et al, 2009), seasonal hormone concentrations (Dawson et al, 2009;Small and Schoech, 2015) or immunity (Hasselquist, 2007) lead to different relationships between coloration and immunity in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that brighter white females obtain nest sites located closer to prime foraging areas and are in better condition and able to mount a stronger immune response as a result. At a proximate level, it is possible that sex differences in the timing of molt (Hemborg, 1999;Dawson et al, 2009), seasonal hormone concentrations (Dawson et al, 2009;Small and Schoech, 2015) or immunity (Hasselquist, 2007) lead to different relationships between coloration and immunity in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin levels drop at the end of the parental phase when parental activities decrease or even stop and the post-breeding molt life-history stage starts a few days after (Crossin et al, 2012). For instance, Deviche et al (2000) showed that both the post-breeding decrease in prolactin levels and the onset of molt occur earlier in young Dark-eyed juncos relative to older juncos and Dawson et al (2009) found that both the decrease in prolactin levels and the onset of molt were delayed in males relative to females in mute swans. Dawson and Fig.…”
Section: Prolactin Stress and The Onset Of Moltmentioning
confidence: 99%
“…Prl can control skin molting in newts (Dent et al 1973) and feather molting in avian species (Dawson and Sharp 1998;Dawson et al 2009;Crossin et al 2012). Seasonal Prl in combination with other hormones is thought to modulate annual changes in hair growth of several species, including sheep, deer, and voles (Duncan and Goldman 1984;Curlewis et al 1988;Smale et al 1990;Dicks et al 1996;Nixon et al 2002;Randall 2007).…”
Section: Prl: a Conserved And Global Regulator Of Tissue Regenerationmentioning
confidence: 99%
“…In humans, patients with elevated serum Prl levels (or hyperprolactinemia) can experience hair loss (Orfanos and Hertel 1988;Foitzik et al 2009;Lutz 2012). Additionally, Prl has been implicated in the regulation of epidermal appendage growth in several avian and mammalian species (Duncan and Goldman 1984;Pearson et al 1996;Dawson and Sharp 1998;Nixon et al 2002;Dawson et al 2009). Prl receptors (Prlrs) are expressed within the HF in both mice and humans, and Prl can induce follicle death in cultured skin tissue from both species (Foitzik et al 2003(Foitzik et al , 2006.…”
mentioning
confidence: 99%